MEANS OF EXPRESSING FOLK LIFESTYLE AND NATIONAL MENTALITY IN WORKS OF ART. (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
this article discusses metaphors, similes, realia, lacunae, which are considered as irreplaceable units, and other units, which are considered means of expressing mentality from a national-cultural point of view, based on the content of the literary text.